Thiol/disulfide formation associated with the redox activity of the [Fe3S4] cluster of Desulfovibrio gigas ferredoxin II. 1H NMR and Mossbauer spectroscopic study - Macedo, A. L. (1994)
NIGMS NIH HHS (GM-41482)